Utility of triphenylphosphine dihalides in organic reactions: esterification using triphenylphosphine dibromide as the dehydrating agent - Lajis, Md Nordin (Universiti Pertanian Malaysia, 1985)
A new esterification method was investigated using triphenylphosphine dibromide as a dehydrating agent. This investigation has established that the method is useful when the acid is aromatic or arylallylic. That primary and secondary alcohols esteTZfy acid satisfactorily whereas tertiary alcohols fail to react was also established in this experiment.